Formation during the Period of Temporary Vows According to the 1983 Code and the Subsequent Holy See Documents - Awiti, Marren Rose A. (Studia canonica, 2017)
The Church recognizes that novitiate formation is insufficientn to prepare religious to attain the maturity necessary for permanent commitment. Therefore, the Church directs that, after first profession, formation of religious is to continue and be perfected (cf. c. 659 § 1). Additionally, the Church requires that each institute draw up a ratio for post-novitiate formation which specifies its structure and duration in accord with universal norms, while permitting adaptations of aspects that may require revision as a result of new needs and realities. The Church has legislated norms on post-novitiate formation which specify its aims, dimensions and pedagogy (cc. 659-661) and has issued subsequent documents with further directives on the challenges facing formation in the post-conciliar period. Therefore, the updating of the ratio is to take into account both the provisions of universal law and the directives found in related post-conciliar documents. The study gives an analysis of the norms on formation during temporary vows as presented in the 1983 Code and the subsequent Holy See documents to expose their deeper meaning in view of offering a resource for religious institutes in need of updating their post-novitiate formation programme.